A new genus and species and additional reports of the South American native ungulates Proterotheriidae (Mammalia, Litopterna) in the Late Miocene of Uruguay. (October 2020) - Corona, Andrea; Badín, Ana Clara; Perea, Daniel; Ubilla, Martín; Schmidt, Gabriela Inés
Abstract: An exhaustive comparative analysis of the recently found cranial, dental and postcranial remains, in the context of the South American native ungulates Proterotheriidae was conducted. A new genus and species of the Family Proterotheriidae, Pseudobrachytherium breve, is reported. The new taxon is based on a complete cranium of medium size, slender, with the complete dentition preserved. It has a new combination of features: a curved dorsal plane at the level of the parietals, premaxilla anteriorly projected (not sagitally diverging), rostral border of the orbit at the level of M1, occipital condyles in the same plane of the basicranium, posteriorly projected, incisors anteriorly projected in a 120° angle with the occlusal plane, M2 with slender hypocone, barely separated from the protocone by a subtle posterior groove and with conspicuous conical metaconule, quite lingually located, very closely to the hypocone. In addition, the first record of Neobrachytherium outside Argentina and other proterotheriid tarsal remains are documented. The fossils herein described were exhumed from sediments of the Camacho Formation, Late Miocene of Uruguay. This study increases the mammalian diversity for this unit and confirm the peak of diversity of the family in the Huayquerian Age/Stage. Highlights: A new genus and species of the Family Proterotheriidae (Mammalia, Litopterna) Pseudobrachytherium breve, is reported. The new taxon is based on a complete cranium of medium size, slender, with the complete dentition preserved. The first record of Neobrachytherium outside Argentina and other proterotheriid indet. are documented. This study increases the mammalian diversity for the Camacho Formation (Late Miocene, Uruguay).